Challenges and prospects of communal service governance - TEKELEHAIMANOT, Assefu Gebreamlak (KDI School, 2015)
Today’s world is typified by a rapid urbanization. On the account of a considerable difference in socio economic conditions between urban and rural areas, people migrate to urban areas in the hope, rather than the actual of obtaining better infrastructure, social services and economic development opportunities. This social condition also imposed governments and city managers to look for adequate housing for the urban poor to mitigate the housing shortage and slum habitation in urban areas. Ethiopian urban centers in general and Addis Ababa city in particular is characterized by rapid population growth which in turn leads to huge housing demand. Taking in to account these human factors, the Ethiopian government is designed a condominium housing program to provide the poor-first housing. The condominium housing development can be considered as a forcing factor to ensure social, economic and political development in a country. However, the governance aspect of the transferred condominium houses and the condo-communal services are militating by several maladministration practices. Therefore, the study employs appropriate literatures to see condo communal service governance in general and particularly the Ethiopian case to evaluate and explore condo-communal service governance in Addis Ababa city. Thus, the study tried to assess and explore the challenges and prospects of condo-communal service governance. Hence, the study’s aim was to assess the factors that affect the condo communal service governance in the condominium sites of Addis Ababa city so as to ensure the equal accessibility of the commons. During the study descriptive and exploratory research types were applied and both primary and secondary sources of date were used through key informant interviews, FGDs, questionnaires and document analysis. The analysis and findings of the study shows that though the Ethiopian government is instituted a district level decentralization to enhance quality public service delivery by empowering local communities by providing housing first, however, poor planning, monitoring and evaluation mechanisms; inadequate participatory and accountability approach , lack of knowledge, skills and commitments; lack of integration among stakeholders; lack of public health, school and recreation centers; poor sanitation and environmental pollution and poor administrative financial resources were of the practical condo communal service governance challenges of the study area. Therefore, government and other respected bodies must work towards insuring on integrated and participatory planning, monitoring and evaluation systems, building public health, school and recreation centers; ensuring sanitation and environmental soundness as well as mobilizing administrative financial resources so as to come up with effective condocommunal service governance.
Thesis(Master) --KDI School:Master of Development Policy,2015